Imaging of tarsal navicular stress injury with a focus on MRI: A pictorial essay. Issue 3 (8th January 2016) - Harris, Guy; Harris, Craig
Summary: Predominantly diagnosed in athletes, stress fracture of the tarsal navicular is becoming increasingly recognised by clinicians as a cause of midfoot pain. Delayed diagnosis can increase the significant morbidity associated with this condition. Consequently the role of MRI is increasing, given the potential to identify a stress reaction in the navicular prior to the development of a discrete stress fracture. It is necessary for radiologists to be familiar with the typical and atypical appearances of this important condition.